Air convection in snow cover of sea ice - P. V. Bogorodskiy; V. A. Borodkin; V. Yu. Kustov; A. A. Sumkina (Лëд и снег, 2020)
For the first time, data on stability of stationary convective filtration within infinite horizontal layer of snow covering the flat surface of floating ice is presented in this article. An analytical solution of the linearized problem was obtained with the use of the Galerkin method, and the parametric analysis of the problem was performed. It was found that the stability criteria (Rayleigh filtration numbers) obtained with consideration for the heat exchange of snow cover with the atmosphere did not exceed the known value of 4π2 for a horizontal porous layer with impermeable isothermal boundaries. As expected, the interaction with the atmosphere has the most significant impact on the critical Rayleigh numbers, while influence of variations in snow density and ice thickness and the thickness of the underlying layer of ice are small. Based on data of ice and meteorological observations made in the winter of 2015/16 in the Western part of the Laptev Sea together with calculations of the fast ice evolution, the values and temporal variability of temperature gradients and the Rayleigh numbers in the snow cover were obtained using a thermodynamic model. It was found that both, the model and observed magnitudes, exceeded their critical values determined by solving the stability problem. The conclusion is made that the convective regime of the heat transfer does really exist in the snow cover, and thus its contribution to the thermal and mass balance of sea ice during winter period should be taken into account.